2013
DOI: 10.1021/ie401810n
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of a Novel Gas Switching Combustion Reactor for Power Production with Integrated CO2Capture

Abstract: This paper experimentally demonstrates the feasibility of a novel Gas Switching Combustion (GSC) reactor as an alternative to the traditional Chemical Looping Combustion (CLC) process for power production with integrated CO2 capture. Whereas the CLC process circulates an oxygen carrier material between two fluidized bed reactors where it is exposed to separate fuel and air streams, the GSC concept employs a single dense fluidized bed reactor where the oxygen carrier is periodically exposed to fuel and air stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
1
36
1
Order By: Relevance
“…Design and scale‐up of pressurized dual CFB systems is likely to pose important technical challenges related to the achievement of a large solids circulation rate which must be tightly controlled in order to maintain the species and energy balance between the two reactors. For this reason, several alternative reactor configurations have been proposed to simplify the reactor scale‐up process such as packed‐bed CLC (PBCLC) 16, 17, gas switching combustion (GSC) 18–20, and the rotating reactor 21. However, these process concepts also have some disadvantages such as the dynamic nature of the PBCLC and GSC concepts, thus requiring a large assembly of reactors operating in parallel with outlet streams regulated by a high‐temperature valve system, as well as significant gas leakage challenges for the rotating bed.…”
Section: Introductionmentioning
confidence: 99%
“…Design and scale‐up of pressurized dual CFB systems is likely to pose important technical challenges related to the achievement of a large solids circulation rate which must be tightly controlled in order to maintain the species and energy balance between the two reactors. For this reason, several alternative reactor configurations have been proposed to simplify the reactor scale‐up process such as packed‐bed CLC (PBCLC) 16, 17, gas switching combustion (GSC) 18–20, and the rotating reactor 21. However, these process concepts also have some disadvantages such as the dynamic nature of the PBCLC and GSC concepts, thus requiring a large assembly of reactors operating in parallel with outlet streams regulated by a high‐temperature valve system, as well as significant gas leakage challenges for the rotating bed.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation model of the engineering drawing method is as follows. (19) where E F,tot , E P,tot and E D,other are the total input exergy of the system, the total output exergy of the system, and the total exergy destruction of other devices than the reactor x. By drawing of a curve of E F,tot À E P,tot with respect to E D,other , the researchers found that when E D,other ¼ 0, the intercept of the curve on the y-axis is equal to the endogenous exergy destruction of the reactor x.…”
Section: Establishing An Exergy Destruction Process Modelmentioning
confidence: 99%
“…9 According to relevant studies, pressurization has a lot of benets to the CLR process, such as improving the conversion rate of carbon, increasing the combustion efficiency, improving the purity of CO 2 captured and reducing the total capital cost of hydrogen production. [19][20][21] However, the CFBR has obvious disadvantages in pressurization. This is because with the increase of pressure, the efficiency of cyclone separator would decrease, while and the destruction of OC particles would increase.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several alternative CLC configurations have been proposed to overcome the challenges of the pressurized dual CFB CLC system. These include gas switching technologies [7,8], rotating bed reactors [9,10], packed bed chemical looping [11,12], and internally circulating reactors (ICRs) [13][14][15], which will be the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%